Answer 6 is and exponential, but I don’t know what 7 is, sorry
Answer:
-5
Step-by-step explanation:
its the same as adding positive numbers but with a minus sign so -3+(-2)= -5
The given ratios 3: 5 and 15: 25 are equal. Because when you divide the ratio 15: 25 by 5 on both numerator and denominator, the first ratio 3: 5 can be obtained. Similarly, when you multiply the first ratio 3: 5 by 5, the ratio 15: 25 can be obtained.
1.77245385
that is the answer
Answer:
-5^x + 3x - 2.
Step-by-step explanation:
(f - g) (x) = f(x) - g(x)
= -5^x - 4 - (-3x - 2)
= -5^x - 4 + 3x + 2
= -5^x + 3x - 2.